Effect of risk management, management support, internal audit and quality control on fraud mitigation in the Libyan banking sector - Alazzabi, Waled Younes (2020)
In recent years, the occurrence of financial crimes in the region of Middle Eastern and North Africa (MENA) have raised regulators’ concern for the need to manage the consequences of these crimes. Particularly, in the context of Libya, the level of financial crimes has increased in the banking sector, nonetheless, there is a little empirical research attempting to solve such a serious problem. This study is, therefore, made for mitigating fraud occurrence in the Libyan banking sector guided by Stakeholder Theory and Control Balance Theory. The study examines the effect of two independent variables, namely, risk management and management support on fraud mitigation. Internal audit activities and internal control quality are employed as two crucial mediators between risk management, management support, and fraud mitigation. Quantitative research method was employed to examine the hypothetical relationships among the variables. The questionnaires were sent to 389 internal auditors working in the Libyan banking sector who were randomly selected and purposive sampling procedure was also used for choosing the respondents based on their nature of work and knowledge. A total of 230 of completed questionnaires were found usable. Data was analysed using Structural Equation Modelling-Partial Least Square (SEM-PLS). The results of the study interestingly revealed insignificant and positive effect of risk management and management support on fraud mitigation. The study results indicated significant mediating effect of internal audit activities on the relationship between risk management, management support, and fraud mitigations. Simultaneously, internal control quality revealed significant mediating effect on the relationship between risk management, management support, and fraud mitigation. This study that is one of the first empirical studies in emerging economics that offers new insights, enhances our understanding, and contributes to theory development through introducing activities of internal audit and quality control as two mediators between risk management, management support, and fraud mitigation. This study framework is a useful blueprint and can benefit banks in their fight against fraud. The study findings also contribute to the development of corporate governance guidelines established by the Central Bank of Libya.